A Model of a Quantum Particle in a Quantum Environment: A Numerical Study (Communications in Computational Physics, 2018)
We define and investigate, via numerical analysis, a one dimensional toy-modelof a cloud chamber. An energetic quantum particle, whose initial state is a superpositionof two identical wave packets with opposite average momentum, interactsduring its evolution and exchanges (small amounts of) energy with an array of localizedspins. Triggered by the interaction with the environment, the initial superpositionstate turns into an incoherent sum of two states describing the following situation: orthe particle is going to the left and a large number of spins on the left side changed theirstates, or the same is happening on the right side. This evolution is reminiscent of whathappens in a cloud chamber where a quantum particle, emitted as a spherical wave bya radioactive source, marks its passage inside a supersaturated vapour-chamber in theform of a sequence of small liquid bubbles arranging themselves around a possibleclassical trajectory of the particle.